Запорізькій державній інженерній академії - 50! (Zaporizhzhia Historical Review, 2021)
The article dwells upon the period of Zaporizhzhya State Engineering Academy formation, exploring the peculiarities of its pedagogical, methodical and scientific activities. In 1959 the training of specialists at the night-faculty of Dnepropetrovsk metallurgical institute has started in Zaporizhzhya. Due to the fruitful activities of the Head of the faculty, Yuriy Michailovich Potebnya, in 1965 the night-faculty had been reorganized to Zaporizhzhya branch of Dnepropetrovsk metallurgical institute. The branch served as a basis for organizing Zaporizhzhya State Engineering Academy in 1975.